1991
DOI: 10.1007/bf00118861
|View full text |Cite
|
Sign up to set email alerts
|

Effects of contrasting fertilization and moisture regimes on biomass, nutrients, and water relations of container grown red pine seedlings

Abstract: Application. Exponential fertilization of red pine seedlings grown under limited irrigation decreased shoot/root ratio, increased root nutrient reserves and enhanced drought avoidance properties when compared to conventional fertilization. Enhanced preconditioning from exponential fertilization may promote outplanting performance.Abstract. Red pine seedlings were grown for 16 weeks under contrasting fertilization (conventional, exponential) and moisture (wet, moist, dry) regimes to assess preconditioning effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 16 publications
1
27
0
1
Order By: Relevance
“…Several previous studies have also reported a positive effect of water stress on nutrient and starch concentration [20,28]. This response has been explained because growth is depressed earlier by drought than are photosynthesis or nutrient absorption [11,17] …”
Section: Resultsmentioning
confidence: 97%
“…Several previous studies have also reported a positive effect of water stress on nutrient and starch concentration [20,28]. This response has been explained because growth is depressed earlier by drought than are photosynthesis or nutrient absorption [11,17] …”
Section: Resultsmentioning
confidence: 97%
“…In contrast, the concentrations of P, Ca, S, Mn and Na were markedly lower in the -5 and -10 kPa irrigation treatments . This may have been due to reduced water supply, which resulted in lower concentrations of nutrients in the growth medium (Timmer and Miller 1991) and/or decreased water and ion conductivity from the peat medium to the roots (Orlander and Due 1986ab;Heiskanen 1993c) . On the other hand, the reduced concentrations of N in the wet irrigation treatment may indicate increased leaching or dilution of N due to high water content .…”
Section: Resultsmentioning
confidence: 99%
“…Lahde and Savonen 1983 ;Bassman et al . 1989 ;Timmer and Armstrong 1989 ;Timmer and Miller 1991) . In particular, little is known about the effects of contrasting irrigation regimes on the actual water and aeration conditions in peat media and subsequent influences on the development of containerized Scots pine (Pinus sylvestris L.) seedlings .…”
Section: Introductionmentioning
confidence: 99%
“…We tested the following working hypotheses: (1) Under high nutrient availability, plant C/N balance decreases and plant growth will be enhanced until being carbon-limited; in such circumstances, carbohydrate reserves will be low, while nitrogen will be in excess and therefore stored. (2) As water stress limits both carbon and nitrogen uptake [42,44], larger water availability is expected to increase plant growth without altering plant C/N balance. (3) Under higher resource availability, the fastest-growing species (i.e.…”
Section: Introductionmentioning
confidence: 99%